Infrastructure investment and travel time - KOH, Yumi (Institutional Knowledge at Singapore Management University, 2020)
We examine additional travel time that arises as reconstruction of non-functioning bridges gets delayed. Our simulations show that the extent to which a budget increase reduces such additional travel time is rather modest. We show that a substantial portion of the unsolved travel time results from budgetary allocations.